The Swedish economy - Bosworth,Barry; Rivlin, Alice M. (Washington, D.C. : Brookings Institution, 1987)
Examines economic conditions and policies in Sweden. Topics include adjusting to slower economic growth, labor markets, taxation, the public sector, and Swedish political foundations.
Includes index.
kjo 17/01/2019
Loans
Keywords: Alice M Rivlin; Economic history; Economic policy; Economic conditions; Sweden